A Comparative linguocultural study of English and Uzbek proverbs (Journal of Pedagogical Inventions and Practices, 2026)
This article examines English and Uzbek proverbs from a linguocultural perspective. By comparing metaphorical structure, cultural values, and pragmatic use, the study highlights both shared human universals and culturally specific worldviews. The findings reveal that while both languages value prudence and moral conduct, English proverbs tend to emphasize individualism and instrumental rationality, whereas Uzbek proverbs prioritize social harmony, respect, and collectivist ideals